2015
DOI: 10.1039/c5ra11093a
|View full text |Cite
|
Sign up to set email alerts
|

Non-corrosive green lubricants: strengthened lignin–[choline][amino acid] ionic liquids interaction via reciprocal hydrogen bonding

Abstract: A series of novel green lubricants with dissolved lignin in [Choline][Amino Acid] ([CH][AA]) ionic liquids (ILs) have been synthesized in this work. The effect of lignin on the thermal and tribological properties of the lignin/[CH][AA] lubricants were systematically investigated by means of thermogravimetric analysis, differential scanning calorimetry, and friction and wear tester. The lignin in [CH][AA] has been demonstrated effective additive to improve thermal stability, reduce wear rate and stabilize frict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 35 publications
(44 reference statements)
1
58
0
Order By: Relevance
“…The halogen-, sulfur-, and phosphorus-free ILs were more prone to form a physically adsorbed film on friction pairs. This result is in good agreement with those reported previously [23,24,30].…”
Section: Tribological Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…The halogen-, sulfur-, and phosphorus-free ILs were more prone to form a physically adsorbed film on friction pairs. This result is in good agreement with those reported previously [23,24,30].…”
Section: Tribological Propertiessupporting
confidence: 83%
“…Several studies have reported the preparation of novel [Ch][AA] ILs, and their potential applications in various fields have been investigated [28,29]. Recently, Mu and coworkers have reported lignin- [Ch][AA] ILs as noncorrosive green lubricants [30]. Nevertheless, to the best of our knowledge, few systematic studies on the structure and properties of Ch-based ionic liquids as environmentally friendly lubricants have been reported.…”
Section: Introductionmentioning
confidence: 94%
“…The addition of lignin enhanced the thermal stability and improved the antiwear properties and friction stability of steel. [176] The lubricating properties were further improved by introducing nitrogen and phosphorus elements into the lignin structure. This resulted in augmented hydrogen-bonding density between the additive and ionic liquids, which led to stronger adhesion of the lubricating layer to the metal surface.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Among others, Vladimir Totolin, Ichiro Minami, Pranesh Aswath, and Jun Qu have worked on halogen‐free ILs as base oils and additives, In this direction, Bharat Bhushan has provided a review on green molecular lubrication. Moreover, Yijun Shi has proposed noncorrosive green ILs, and Stefan Stolte has been working on the development of biological ILs for more than 10 years. Despite the intense work in the field, no systematic studies in relation to the performance and toxicity evaluation of ILs have been carried out.…”
Section: Introductionmentioning
confidence: 99%